TiO2 thin films for photocatalytic oxidation of pharmaceutical compounds - Turra, Claudia; Mortari, Sergio Roberto; Bulhões, Luis Otavio de Sousa (Disciplinarum Scientia | Naturais e Tecnológicas, 2017)
Degradation of amoxicillin was investigated in aqueous solution by photocatalysis on TiO2 thin film under UV (365 nm) radiation. The TiO2 thin film is a pure anatase phase as shown in the X ray diffraction analysis. Enhancement of photocatalysis kinetic rate by addition of NaOH was also evaluated. No significant degradation occurred by UV radiation per se and a low adsorption affinity between the antibiotic molecule and TiO2 surface was observed. pH had a significant effect on antibiotic degradation and the photocatalytic reactions followed a zero-order kinetics and the rate constants (k) were 8.02×10-4 mol L-1 min-1 to 7.45×10-3 mol L-1 min-1 for amoxicillin in pH 6 and 11, respectively.